THE COMMUNITY GROUPS OF LISBON AS “COMMONS” - Amaro, R.; Ferreira, B. (1st INTERNATIONAL CONFERENCE ON SOCIAL SOLIDARITY AND THE COMMONS, 2020)
A Community Group (CG) is essentially a platform for diagnosis, negotiation and action, involving residents, public administration, public services and NGOs, with the aim of identifying, tackling and solving local problems and challenges, that is, to promote the Wellbeing and “Buen Vivir”. To this end, it must combine the principles of Participation (i.e. the active involvement of the Community, especially the "voiceless") and Partnership (i.e. interinstitutional forms of cooperation) in a new form of Participatory and Shared Governance. They CGs are, therefore, processes of co-Knowledge, co-Management and co-Construction of Community Development and Common Good. In this sense, they can promote, construct and manage various types of "Commons", understood as co-Activities (see Dardot & Laval, 2014), such as: the production of Knowledge (negotiated looks into local problems and potentialities); the transformation of Public or Private Spaces into Commons (by their use and management); the “common action” towards the identified problems and needs; the production, use and sharing of Cultural values (whether tangible or intangible), assumed as a Common Good. In all these processes, more importantly than ownership, is the emerge of communal forms of use and co-management. This helps create and advance the nature of the Community, that is, of Common, which CG can facilitate and empower, if they are effectively democratic spaces for deliberation and decision.